2017
DOI: 10.1177/1475725717712785
|View full text |Cite
|
Sign up to set email alerts
|

Does A Brief Mindfulness Intervention Impact Quiz Performance?

Abstract: Mindfulness practices improve cognition, emotional balance, and well-being in clinical and non-clinical populations. The bulk of mindfulness research in higher education has focused on improving psychological and cognitive variables, leaving academic performance largely unexplored. We investigated the effects of a brief mindfulness intervention on quiz performance in two sections of an undergraduate upper-level human development class (N ¼ 67). We used a between-group experimental design (waiting control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
0
26
1
Order By: Relevance
“…Several experimental studies assigned a group of students 1 to either 5-20-minute breathing meditation or an active or passive control condition prior to a regular university/college course and assessed retention of course content via quiz performance at the end of the session. With the exception of Baranski and Was (2019), all studies observed superior quiz performance in the mindfulness meditation group (Ramsburg and Youmans, 2014;Calma-Birling and Gurung, 2017;Bennett et al, 2018;Lin and Mai, 2018), indicating that brief mindfulness inductions can boost short-term academic performance. Some of these studies (Calma-Birling and Gurung, 2017; Lin and Mai, 2018; Baranski and Was, 2019) provided such mindfulness inductions at the beginning of each course session over several weeks and explored whether this would lead to superior long-term academic success, indexed by performance in exams that tested the content of multiple course sessions.…”
Section: Introductionmentioning
confidence: 96%
“…Several experimental studies assigned a group of students 1 to either 5-20-minute breathing meditation or an active or passive control condition prior to a regular university/college course and assessed retention of course content via quiz performance at the end of the session. With the exception of Baranski and Was (2019), all studies observed superior quiz performance in the mindfulness meditation group (Ramsburg and Youmans, 2014;Calma-Birling and Gurung, 2017;Bennett et al, 2018;Lin and Mai, 2018), indicating that brief mindfulness inductions can boost short-term academic performance. Some of these studies (Calma-Birling and Gurung, 2017; Lin and Mai, 2018; Baranski and Was, 2019) provided such mindfulness inductions at the beginning of each course session over several weeks and explored whether this would lead to superior long-term academic success, indexed by performance in exams that tested the content of multiple course sessions.…”
Section: Introductionmentioning
confidence: 96%
“…A lack of difference between groups on cognitive performance may be explained by recent evidence suggesting that brief MM may only result in immediate, short-term cognitive benefits (Calma-Birling & Gurung, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Examining the effects of brief MM on test performance in an undergraduate sample, a sevenweek study found that five-minute inductions of MM boosted quiz grades and short-term knowledge retention, but failed to impact longterm test scores (Calma-Birling & Gurung, 2017). As such, smaller doses of MM may only give rise to immediate, short-term cognitive performance effects (Calma-Birling & Gurung, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through cognitive reappraisal interventions, there was a focus on normalizing emotions in a college classroom setting [17]. Mindful ways of approaching emotional experiences were introduced, rather than techniques for reappraisal [14]. PPIs were used for students taking a positive psychology course [31].…”
Section: Unique Methodsmentioning
confidence: 99%